2009
DOI: 10.5194/acpd-9-18511-2009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modeling the transport of very short-lived substances into the tropical upper troposphere and lower stratosphere

Abstract: Abstract. The transport of very short-lived substances into the tropical upper troposphere and lower stratosphere is investigated by a three-dimensional chemical transport model using archived convective updraft mass fluxes (or detrainment rates) from the European Centre for Medium-Range Weather Forecast's ERA-Interim reanalysis. Large-scale vertical velocities are calculated from diabatic heating rates. With this approach we explicitly model the large scale subsidence in the tropical troposphere with convecti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 26 publications
1
41
0
Order By: Relevance
“…Aschmann et al, 2009;Hossaini et al, 2010;Liang et al, 2010;Tegtmeier et al, 2012). In contrast to longer-lived source gases, measurements of these VSLS from the planetary boundary layer can therefore not be used to constrain the amount of halogen input into the stratosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Aschmann et al, 2009;Hossaini et al, 2010;Liang et al, 2010;Tegtmeier et al, 2012). In contrast to longer-lived source gases, measurements of these VSLS from the planetary boundary layer can therefore not be used to constrain the amount of halogen input into the stratosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies by Dvortsov et al (1999) and Nielsen and Douglass (2001) calculated a maximum of 1.8 pptv and 1.1 pptv Br y , respectively, in the stratosphere from bromoform (CHBr 3 ). More recent modeling studies by Kerkweg et al (2008), Gettelman et al (2009), Aschmann et al (2009) and Hossaini et al (2010) suggested that CHBr 3 and CH 2 Br 2 contribute significant amounts of reactive bromine to the lower stratosphere, with the calculated contribution varying between ∼2-3 pptv among individual studies. One exception is the modeling study by Warwick et al (2006) which presented a detailed emissionbased modeling analysis of all five major VSL oceanic bromocarbons, including CHBr 3 , dibromomethane (CH 2 Br 2 ), bromodichloromethane (CHBrCl 2 ), dibromochloromethane (CHBr 2 Cl), and bromochloromethane (CH 2 BrCl).…”
mentioning
confidence: 99%
“…The broad spatial and temporal coverage of these measurements lends more confidence in the robustness of our derived results. Secondly, unlike many previous modeling studies that assume a constant wash-out lifetime of Br y (10-days in Dvortsov et al, 1999, Nielsen andDouglass, 2001;Warwick et al, 2006;Hossaini et al, 2010; 0 to indefinite days in Sinnhuber and Folkins, 2005) or a relative simple washout process (Aschmann et al, 2009), we implement a detailed wet deposition scheme that includes scavenging in convective updrafts and rainout/washout in large-scale precipitation. This is to assure a more realistic representation of the impact of large-scale/convective transport on the highly soluble Br y .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that halogens in the form of very short-lived halocarbons (VSLH) and volatile organic compounds (VOC) may affect the oxidizing capacity of the troposphere. These compounds when transported up into the troposphere and stratosphere, undergo photolysis and the halogens which are released, result in ozone depletion in the stratosphere and influence climate change (Aschmann et al, 2009). Examples are brominated and chlorinated halocarbons which indirectly affect temperature (Forster and Joshi, 2005) by ozone depletion.…”
Section: Marine Emissions Of Halogenated Compounds In the Tropicsmentioning
confidence: 99%